Sistem Pemidanaan Indonesia Ditinjau dari Pendekatan American Legal Realism dan Scandinavian Realism - Selviria Selviria (Simbur Cahaya, 2018)
Criminal law aims to prevent or inhibit the actions of the community that are not in accordance with applicable legal rules. The problem of criminal conviction or imposition is very interesting. Not because of the good enforcement process but the poor views of the public (society) of Indonesia and the international community. Judge's decisions are often considered not to fulfill a sense of justice for the community, which in this case is the case of Grandma Minah who was found guilty of stealing 3 cocoa fruits. If the case is compared to the imposition of a sentence on cases of corruption, then this is felt to be inappropriate. Law enforcement in Indonesia is likened to a sharp knife down but blunt up. Against this criminal imposition it can be seen also from American realism and Scandinavian realism towards criminal prosecution, in this case American realism views the law based on the judge's decision, which is inversely proportional to the view of Scandinavian realism. The method in this paper is interdisciplinary with a socio-legal studies approach, namely by using an approach that focuses on seeing the law through a combination of normative analysis [juridical legal norms] and non-legal science approaches. The nature of socio-legal is prescriptive translation by providing solutions to legal problems, combining normative analysis and no-legal / social aspects approaches. From the research it can be concluded that the realist approach has been charged with causing a lot of confusion and overload of the role of judges in forming and making laws. Such a view assumes that law is not what is carried out by a court, but a court is an institution that implements the law. If the judge tends to follow the law, it will be very easy to predict what the judge has decided in many cases. The legal definition that states the law as what is decided by the court, is the same as stating that the drug is what is written on prescription paper by a doctor